Intention‐to‐treat analysis of percutaneous endovascular treatment of hepatic artery stenosis after orthotopic liver transplantation. Issue 7 (July 2016) - Rajakannu, Muthukumarassamy; Awad, Sameh; Ciacio, Oriana; Pittau, Gabriella; Adam, René; Cunha, Antonio Sa; Castaing, Denis; Samuel, Didier; Lewin, Maïté; Cherqui, Daniel; Vibert, Eric
Abstract : Hepatic artery stenosis (HAS) is a rare complication of orthotopic liver transplantation (LT). HAS could evolve into complete thrombosis and lead to graft loss, incurring significant morbidity and mortality. Even though endovascular management by percutaneous transluminal angioplasty ± stenting (PTA) is the primary treatment of HAS, its longterm impact on hepatic artery (HA) patency and graft survival remains unclear. This study aimed to evaluate longterm outcomes of PTA and to define the risk factors of treatment failure. From 2006 to 2012, 30 patients with critical HAS (>50% stenosis of HA) and treated by PTA were identified from 870 adult patients undergoing LT. Seventeen patients were diagnosed by post‐LT screening, and 13 patients were symptomatic due to HAS. PTA was completed successfully in 27 (90%) patients with angioplasty plus stenting in 23 and angioplasty alone in 4. The immediate technical success rate was 90%. A major complication that was observed was arterial dissection (1 patient) which eventually necessitated retransplantation. Restenosis was observed in 10 (33%) patients. One‐year, 3‐year, and 5‐year HA patency rates were 68%, 62.8%, and 62.8%, respectively. Overall patient survival was 93.3% at 3 years and 85.3% at 5 years. The 3‐year and 5‐year liver graft survival rates were 84.7% and 64.5%, respectively. No significant difference was observed in patient and graft survivals between asymptomatic and symptomatic patients after PTA. Similarly, no difference was observed between angioplasty alone and angioplasty plus stenting. In conclusion, endovascular therapy ensures a good 5‐year graft survival (64.5%) and patient survival (85.3%) in patients with critical HAS by maintaining HA patency with a low risk of serious morbidity (3.3%). Liver Transplantation 22 923–933 2016 AASLD